Wireless infrared headset communications for vision impaired persons in multi-user environments - Pasquale, Andrew (Curtin University, 2009)
A dual communications systems with application to call centre environments has been developed to aid visually impaired persons. The needs of the visually impaired in such a situation are for wire-less communications as wires connecting the headphone easily become tangled and this is a difficulty for the visually impaired to rectify and is distracting from their work. The proposed system utilises infrared communications for much of the normal traffic. It is stereo with one channel devoted to the enquirer audio channel and one to an aural description of the computer screen being used to perform the call centre actions. This system needs to be high bandwidth, but to achieve that in this environment demands directivity. Hence if the the operator turns away from the screen they lose connectivity. To overcome that, a second, lower bandwidth radio frequency communications system is proposed that keeps the operator in touch with call centre operations. A working test bed was created to assess the suitability of the infrared communications in such a headset. It was found found that it performed satisfactorily within the environment although its effectivness was limited by the users. natural body movements. This was more than compensated for by its superior security and sound quality.